Effect of Counselling Sessions on Achievement of Students in English at Senior Secondary Level - Singh, Vikramjit; Jha, Jay Kumar (American Journal of Social Sciences and Humanities, 2019)
Languages play a vital role in human life. Language is a means of communication. It is the basis of human progress. It is the flesh and blood of human culture. Without language civilization could hardly even have begun and certainly could never have attained its higher forms. The teaching and learning of English in our schools are at very chaotic state. We have daily compulsory periods in English but our students passing out of schools perform very poorly in the subject and its practices. Counselling services play an important part in the development of the human being as an individual and education is the foundation for the development of human potential. Although the teaching-learning situation constitutes the heart of the educational process, yet counselling gives it a more meaningful purpose. The study here throws light upon the impact of counselling sessions on academic achievement of students in English at senior secondary level. The paper here reports the findings on effectiveness of counselling sessions which has been introduced in schools, KendriyaVidayalayas in particular on the achievement in English. The finding presented herewith is an outcome of an experimental research carried forward by the researchers on 72 senior secondary students. The study found out that the students those underwent with counselling sessions performed very well in comparison to the control group. It was also concluded that the effect of counseling sessions were sex as well as stream (science vs. commerce) neutral.